The Impact of Performance Factors on Performance on Quality in Project Implementation - Tedi, Hermawan; Fajarni, Oktavia Futri; Aminudin; Ronald, Marpaung Richo; Darul, Iman; Acep Hidayat (Journal of Educational Management Research, 2025)
This study aims to analyze the impact of various performance factors on contractor performance in the implementation project, as part of the National Police's institutional transformation toward a predictive, responsive, and transparent work system. The performance factors analyzed include managerial competence, work experience, communication, and time management. Using a questionnaire and Partial Least Square (PLS) analysis, the study finds that managerial factors (P-value 0.000) and occupational safety and environment (K3L) (P-value 0.016) significantly influence contractor performance. However, legal and licensing, financial, technical, and social aspects do not show significant effects. The study suggests focusing on improving managerial training and enhancing K3L standards, while also maintaining compliance with licensing and social relationships. This research highlights the importance of management and safety training in educational settings to improve professional performance in construction projects.